ANALISIS PERBANDINGAN KINERJA KEUANGAN PERBANKAN SYARIAH MENGGUNAKAN PENDEKATAN LABA RUGI (INCOME STATEMENT) DAN NILAI TAMBAH (VALUE ADDED STATEMENT) - M. Amrullah Reza P.T; Adityawarman Adityawarman (Diponegoro Journal of Accounting, 2014)
This study aims to analyze whether there are significant differences of Islamic banking financial statements using the income statement approach and value added approach is measured using financial ratios . Financial ratios used in this study is ROA , ROE , LBAP and NPM .Objects used in this study is the financial statements have been audited by an independent auditor in the period 2010 - 2012 of Bank Mega Syariah , Bank Muamalat Indonesia , Bank Syariah Mandiri , BCA Syariah , BRI Syariah , Bank Panin Syariah and the Syariah Bukopin using two approaches is income statement approach and value added approach . The analytical tool used in this study is paired samples test with SPSS 17.00 for Windows.The results of this study indicate that the ratio of ROA , ROE , LBAP and NPM has a significant difference between the income statement approach and value added approach . While the overall performance showed that profabilitas contained significant levels of each difference between the income statement approach and value added approach .